Transformation of Seed Non-Transmissible Hop Viroids in Nicotiana benthamiana Causes Distortions in Male Gametophyte Development - Steinbachová, Lenka; Matoušek, Jaroslav; Steger, Gerhard; Matoušková, Helena; Radišek, Sebastjan; Honys, David (Plants (Basel, Switzerland), 2021)
Viroids are small, non-coding, parasitic RNAs that promote developmental distortions in sensitive plants. We analyzed pollen of Nicotiana benthamiana after infection and/or ectopic transformation with cDNAs of citrus bark cracking viroid (CBCVd), apple fruit crinkle viroid (AFCVd) and potato spindle tuber viroid (PSTVd) variant AS1. These viroids were seed non-transmissible in N. benthamiana. All viroids propagated to high levels in immature anthers similar to leaves, while their levels were drastically reduced by approximately 3.6 × 103, 800 and 59 times in mature pollen of CBCVd, AFCVd and PSTVd infected N. benthamiana, respectively, in comparison to leaves. These results suggest similar elimination processes during male gametophyte development as in the Nicotiana tabacum we presented in our previous study. Mature pollen of N. benthamiana showed no apparent defects in infected plants although all three viroids induced strong pathological symptoms on leaves. While Nicotiana species have naturally bicellular mature pollen, we noted a rare occurrence of mature pollen with three nuclei in CBCVd-infected N. benthamiana. Changes in the expression of ribosomal marker proteins in AFCVd-infected pollen were detected, suggesting some changes in pollen metabolism. N. benthamiana transformed with 35S-driven viroid cDNAs showed strong symptoms including defects in pollen development. A large number of aborted pollen (34% and 62%) and a slight increase of young pollen grains (8% and 15%) were found in mature pollen of AFCVd and CBCVd transformants, respectively, in comparison to control plants (3.9% aborted pollen and 0.3% young pollen). Moreover, pollen grains with malformed nuclei or trinuclear pollen were found in CBCVd-transformed plants. Our results suggest that "forcing" overexpression of seed non-transmissible viroid led to strong pollen pathogenesis. Viroid adaptation to pollen metabolism can be assumed as an important factor for viroid transmissibility through pollen and seeds.
Keywords: male gametophyte; CBCVd; viroid elimination; plant transformation; AFCVd and PSTVd parasitic RNAs; proteomic of viroid infected pollen; Humulus lupulus; Nicotiana benthamiana